Cobalt-Catalyzed Formation of 2-Pyridylzinc Reagents and Their Subsequent Coupling - Linke, Stephanie; Manolikakès, Sofia M.; Auffrant, Audrey; Gosmini, Corinne (Synthesis, 2018)
The preparation of pyridylzinc compounds from the corresponding pyridyl halides using a cobalt catalyst is described. The complex employed features a polydentate N-heterocyclic ligand and allows the reaction to be carried out in the absence of pyridine as co-solvent and also in THF in place of acetonitrile. First cross-coupling attempts are also presented. Satisfactory yields were obtained via a one-pot protocol without the addition of another catalyst.
Keywords: cobalt catalysis; N-heterocyclic ligand; zinc; cross-coupling; pyridines